(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2020)
The detection of new antibiotics and other bioactive microbial metabolites is a benefit step given the rate of the rising multi-drug resistant pathogenic microorganisms. This study aimed to isolate and screen the antimicrobial activity of gram positive bacteria named actinomycetes. The actinomycetes were isolated from near-shore marine sediment that were collected from three different depths at the Libyan Alkhoms coastline. A total of five out of twenty actinomycetes were isolated on different supported medium, whereas, Sabouraud Dextrose Agar was found to exhibit the antagonistic properties of the bioactive compounds produced by actinomycetes isolates. These isolates had shown a clear zone on Mueller-Hinton agar against target microorganisms were considered as actinomycetes labelled from HSEH1 to HSEH20. The antimicrobial properties of these isolates against (Klebcella pneumonia, Escherichia coli, Salmonella typhi, Staphylococcus aureus and Candida albicance were examined by primary screening using spot inoculating method. were examined by primary screening using spot inoculating method. The results that all the five selected isolates were according to biochemical testes found to show inhibitory activity against the target microbes. Generally, HSEH16 isolate showed the highest inhibitory activity against all target pathogenic microbes compared with other selected isolates which have activity however, with different ranges of inhibition zone. Thus, the isolate HESH16 is the best among the other isolates considered to have a broad bacterial spectrum in this study. This isolate could be considered as potential antimicrobial properties of secondary metabolites against strains human pathogens and should be further studied for their human health.